Political determinants of the extensive and intensive margins of international arms transfers - Florian Johannsen; Inmaculada Martínez-Zarzoso (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2013)
The main aim of this paper is to investigate the political determinants of international arms transfers. We distinguish between the decision to exports arms (extensive margin) and the value of the arms exported (intensive margin). A theoretically-justified gravity model of trade augmented with political factors is estimated using a two-stage panel-data approach for 104 exporting countries over the period 1950 to 2007. As main political factors the level of democracy in the trading partners as well as the political orientation of the ruling governments are considered. Furthermore we account for the political differences between trading partners, the political environment differences in their respective regions and the existence of military pacts. The main results indicate that political closeness between countries is an important determinant of transfers in arms and that economic and strategic interests are not the only drivers of the transfers.
Keywords: F14; F51; 330; arms trade; political factors; democracy; conflict; gravity model; military pacts